PASAR MODAL DI INDONESIA DALAM PERSPEKTIF FIKIH MUAMALAH - Muhammad Abdul Ghoni (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2017)
Abstract: Islamic teaching that is a straight path but not a rigid religion, it is a line-giver to the problems encountered by humans in the course of their lives. Muslims should have a concept that contains a way of life to face the development and progress of the times with various problems. One area that is always warm to talk about is the economy. This problem is getting wider, more varied and more complex. It is not uncommon to find it complicated, especially when confronted with Islamic law. One of them is about the capital market. This journal tries to examine from the perspective of jurisprudence about the jala of the existing capital markets. If we look at the system of stock bidding mechanisms in the capital market, it will be clear that there is a similarity with the capital system contained in the conception of Islamic fiqh, known as mudharabah or qirodh. It is seen from the investors, executors, the nature of capital, capital, and profit sharing of the same shape. Thus, the system of buying and selling of shares in the stock market is clearly visible equation with mudharabah in Islamic jurisprudence.